EU and Regulatory Autonomy on the Digital Trade Frontier - Lunde,Tor Magne (2025)
Amid the rapid expansion of the global digital economy, the European Union faces a fundamental tension between promoting digital trade liberalisation and safeguarding its regulatory autonomy. This thesis examines how policy space provisions within the EU's new, standalone Digital Trade Agreements (DTAs) with Singapore and South Korea relate to this strategic challenge. Using a legal doctri-nal and comparative method, this analysis contrasts the DTAs with their predecessor Free Trade Agreements (FTAs) to demonstrate a significant architectural and regulatory evolution. The findings re-veal a strategic shift from the reactive, exception-based model of the FTAs, where regulation is a derogation from trade commitments, to a proactive framework in the DTAs where regulatory autonomy is established as a foundational, overarching principle. The research concludes that these provisions, particularly the horizontal Right to Regulate, not only are strategically crafted legal instruments de-signed to defend and actively preserve, reinforce, and project the EU's regulatory power. They also function as a key tool of the EU's Open Strategic Autonomy, insulating its internal digital acquis (such as the GDPR and DSA) from external trade pressures while simultaneously using market access as leverage to shape global standards. Ultimately, these DTAs fundamentally alter the paradigm of trade policy. Under this new model, trade liberalisation becomes both contingent upon and a mechanism for the external projection of the EU's regulatory autonomy.
Keywords: EU; Law; Digital Trade Agreement; Singapore; South Korea; Trade; Free Trade Agreement; International Digital Trade; WTO; GDPR; Open Strategic Autonomy; Brussels Effect; Right to regulate; Exceptions; Carve-outs; DTA; FTA; EUSFTA; EUSDTA; EUKDTA; EUKFTA; Regulatory autonomy